Association of dietary patterns with serum vitamin D concentration among Iranian adults with abdominal obesity - Payam Sharifan (Elsevier, 2021)
Summary: Introduction: Vitamin D is obtained from dermal synthesis and dietary sources. The serum concentration of 25-hydroxyvitamin D [25(OH)D], may be used to evaluate vitamin D status, and this has been related to different dietary patterns (DPs) in previous studies. The bioavailability of vitamin D may be affected by adiposity. We aimed to investigate the relationship between dietary patterns and serum 25(OH)D in an Iranian population sample with abdominal obesity. Methods: This cross-sectional study was undertaken in 215 adults who were 30–50 years old, and comprised students and employees of Mashhad University of Medical Sciences (MUMS), who had abdominal obesity. Serum 25(OH)D was measured using an enzyme-linked immunoassay method. A 65-item validated food frequency questionnaire (FFQ) and a principal components factor analysis (PCA) method were used to determine major dietary patterns. Results: Two major dietary patterns were identified among the study population using PCA, and were termed “healthy” and “unhealthy”. The healthy dietary pattern was characterized by a high intake of fruits, green leafy vegetables, other vegetables, honey, dairy products, olive oil, nuts, poultry, legumes, and soup and low intake of sugar, tea and solid fats. An unhealthy dietary pattern was characterized by high consumption of carbonated beverages, processed meat, fast foods, snacks, mayonnaise, seafood, red meat, refined grains, pickled foods, coffee, mineral water, potato, liquid fats, and egg. Serum concentrations of 25(OH)D were directly associated with adherence to the healthy dietary pattern (r: 0.170, p<0.05); though, there was no association between unhealthy pattern and serum 25(OH)D level. Conclusion: Serum 25(OH)D level was significantly associated with adherence to a healthy dietary pattern in a sample of Iranian adults in Mashhad city, Iran.